Experimental analysis of vapour-liquid phase equilibria for binary systems of diethyl carbonate with methyl, ethyl, isopropyl, n-butyl and isoamyl acetates at 95 kPa - Bhoi, Bharat R.; Mali, Nilesh A.; Joshi, Sunil S. (Journal of Chemical Thermodynamics, 2020)
Experimental analysis of vapour-liquid phase equilibrium (VLE) for five binary pairs of diethyl carbonate (DEC) with methyl acetate, ethyl acetate, isopropyl acetate, n-butyl acetate and isoamyl acetate was carried out in this study. VLE data were generated experimentally at local atmospheric pressure of 95 kPa in a glass dynamic recirculation still. Reliability of data was checked with the thermodynamic consistency tests by Van Ness, infinite dilution, pure component and mean absolute deviation test. Experimental data was found to be thermodynamically consistent with all tests and data was regressed with Wilson, NRTL and UNIQUAC activity coefficient models to determine binary interaction parameters. Binary pair of DEC with n-butyl acetate has shown azeotropic behaviour with minimum boiling azeotrope and a close boiling behaviour through-out the composition range. No azeotropic behaviour was observed for the rest of the binary pairs. (c) 2020 Elsevier Ltd.
Keywords: Diethyl carbonate; ethyl acetate; Isobaric; Isopropyl acetate; methyl acetate; VLE